2022
DOI: 10.1021/acs.jpcb.2c01021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nonspecific Interactions between Proteins and In Vivo Cytoplasmic Crowders in Facilitated Diffusion of Proteins: Theoretical Insights

Abstract: The binding of proteins to their respective specific sites on the DNA through facilitated diffusion serves as the initial step of various important biological processes. While this search process has been thoroughly investigated via in vitro studies, the cellular environment is complex and may interfere with the protein's search dynamics. The cytosol is heavily crowded, which can potentially modify the search by nonspecifically interacting with the protein that has been mostly overlooked. In this work, we prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Motivated by the findings of the in vitro experiments by Riggs et al, it was proposed that the DBPs locate these target sites on the DNA via a facilitated diffusion mechanism which is comprised of 3D and 1D diffusion modes of the proteins. , With the help of a discrete state stochastic model analyzed using the first passage analysis, Kolomeisky and co-workers developed a minimal model to describe the target search process of a single DBP . In realistic situations, macromolecular bulk crowding occupies about 40% of the cellular matrix. , Using our theoretical results obtained via first passage analysis applied to a discrete-state model, supported by extensive Monte Carlo computer simulations, we were able to determine the conditions that facilitate or hamper the search process in a real cellular environment. …”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Motivated by the findings of the in vitro experiments by Riggs et al, it was proposed that the DBPs locate these target sites on the DNA via a facilitated diffusion mechanism which is comprised of 3D and 1D diffusion modes of the proteins. , With the help of a discrete state stochastic model analyzed using the first passage analysis, Kolomeisky and co-workers developed a minimal model to describe the target search process of a single DBP . In realistic situations, macromolecular bulk crowding occupies about 40% of the cellular matrix. , Using our theoretical results obtained via first passage analysis applied to a discrete-state model, supported by extensive Monte Carlo computer simulations, we were able to determine the conditions that facilitate or hamper the search process in a real cellular environment. …”
Section: Discussionmentioning
confidence: 80%
“… 109 , 110 Using our theoretical results obtained via first passage analysis applied to a discrete-state model, supported by extensive Monte Carlo computer simulations, we were able to determine the conditions that facilitate or hamper the search process in a real cellular environment. 111 113 …”
Section: Discussionmentioning
confidence: 99%
“…In the current theoretical model, the quantified results on the modulation in the target search rates provide an easy handle to gain a deeper insight into the process. The study is found to be suitable to provide a convenient methodology to capture the modulation in the target search rate even in a complex situation such as, in the presence of blocking agents 28,30,39,57 or in a crowded and rearranging disordered media. A natural extension of this work will be the application of a similar theoretical framework to extract testable and quantified predictions to manipulate the target search technique in a more complicated scenario.…”
Section: Author Contributionsmentioning
confidence: 99%
“…1) involving 1D motion along with a 3D diffusion has been theoretically conceptualized to explain the mechanism successfully. 5,[11][12][13][14]24,[28][29][30][51][52][53][54][55][56] The search strategy based on facilitated diffusion thus enables to capture the faster and more efficient target search method and hence seems to provide a reliable general technique for the target search process. Following the analytical model for the facilitated diffusion and expressing the 1D and 3D diffusion timescales with simple scaling arguments based on dimensional analysis, the target search time, t tst can be derived as, 12,[57][58][59][60][61]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation